Factors associated with non-response to naldemedine for opioid-induced constipation in cancer patients: A subgroup analysis - Yuko Kanbayashi; Mayumi Shimizu; Yuichi Ishizuka; Shohei Sawa; Katsushige Yabe; Mayako Uchida (PLoS ONE, 2022)
Background Opioid-induced constipation (OIC) is one of the most common adverse events of opioid therapy and can severely reduce quality of life (QOL). Naldemedine is the orally available peripheral-acting μ-opioid receptor antagonist approved for OIC treatment. However in daily clinical practice, some cancer patients show insufficient control of OIC even while receiving naldemedine. Objective To identify factors associated with non-response to naldemedine in cancer patients. Methods This study retrospectively analyzed 127 cancer patients prescribed naldemedine at Seirei Hamamatsu General Hospital in Japan between November 2016 and June 2021. For the regression analysis of factors associated with OIC, variables were extracted manually from electronic medical records. Naldemedine had been prescribed by the attending physician after the presence of OIC had been defined with reference to Rome IV diagnostic criteria. Naldemedine was evaluated as “effective” in cases where the number of defecations increased at least once in the first 3 days after starting naldemedine. Multivariate logistic regression analysis was performed to identify factors associated with non-response to naldemedine. The data used were from the group of patients who received naldemedine in our previous study. Results Factors significantly associated with non-response to naldemedine included chemotherapy with taxanes within 1 month of evaluation of naldemedine effect (odds ratio [OR] = 0.063; 95% confidence interval [CI] = 0.007–0.568), and addition of or switching to naldemedine due to insufficient efficacy of prior laxatives (OR = 0.352, 95% CI = 0.129–0.966). Conclusion The identification of factors associated with non-response to naldemedine prescribed for OIC may help improve QOL among cancer patients.